Binding and Fluorescent Sensing of Dicarboxylates by a Bis(calix[4]pyrrole)‐Substituted BODIPY Dye. Issue 8 (30th January 2013) - Gotor, Raúl; Costero, Ana M.; Gaviña, Pablo; Gil, Salvador; Parra, Margarita
Abstract: A bis(calix[4]pyrrole)‐substituted BODIPY ditopic receptor1 has been synthesised and characterised. The binding and sensing properties of1 towards several aliphatic and aromatic dicarboxylates have been evaluated by using UV/Vis fluorescence and 1 H NMR spectroscopy. The receptor strongly binds linear α, ω‐dicarboxylates of appropriate lengths (C9 andC10 ) by acting as a cleft. For all dicarboxylates, the binding event is detected by a bathochromic shift in the UV/Vis spectra of the receptor and by strong quenching of its fluorescence. Abstract : The bis(calix[4]pyrrole)‐substituted BODIPY ditopic receptor1 shows high affinity towards linear α, ω‐dicarboxylates of appropriate lengths. The binding event is detected by a bathochromic shift in the UV/Vis spectra of the receptor and by a strong quenching of its fluorescence.